Spatial Distribution of Household Water Contamination Associated with Livestock Waste Along Upstream-Downstream Areas in Ponorogo, Indonesia - Inna Sholicha; Onny Setiani; Nurjazuli Nurjazuli; Apoina Kartini (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2026)
Livestock waste is a major source of environmental pollution in rural Indonesia. In general, livestock sanitation and household water quality are still assessed separately, so understanding of contamination pathways in upstream and downstream hydrological systems remains limited. This study aims to explore the spatial distribution of household water contamination associated with livestock waste sanitation and to classify environmental health risks along an upstream-downstream gradient. An exploratory environmental assessment was conducted in three descriptive sub-districts of Ponorogo Regency, representing the upstream (Pudak), transition (Pulung), and downstream (Sooko) areas. Fifteen household water samples were analyzed for microbiological parameters (total coliforms, Escherichia coli) and chemical parameters (BOD, nitrates, NH3), as well as for secondary data on cattle pen sanitation and river water quality. Data were analyzed descriptively and spatially using semi-quantitative risk classification based on exceeding national quality standards. 58% of cattle pens lacked adequate sanitation. BOD levels reached 14 mg/L (which was 2.33 times higher than the national standard), and NH₃ reached 0.64 mg/L (32 times higher). None of the household water samples were eligible for total microbiological testing. Gradients of increased contamination in upstream areas (Pudak) with moderate pollution loads, transition areas (Pulung) with moderate levels of contamination due to upstream exposure, and downstream (Sooko) with high contamination. Contamination patterns show an increased risk gradient from upstream to downstream waste sources. Improving cattle pen sanitation and livestock waste management in upstream areas is needed as a priority for environmental health interventions.